Evaluation of the Attitudes and Opinions of Veterinary School Students on Distance Education during the COVID-19 Pandemic - Aslim, Goekhan; Tekindal, Mustafa Agah; Yigit, Ali; Sanal, Sule; Mentes, Ayse (Univ Toronto Press Inc, 2024)
This study aimed to determine the attitudes and opinions of the students of veterinary schools in Turkey regarding distance education during the COVID-19 pandemic. The study was conducted in two stages: (1) develop and validate a scale for assessing Turkish veterinary students' attitudes and opinions regarding distance education (DE) (n = 250 students; one veterinary school) and (2) widespread use of this scale amongst veterinary students (n = 1,599 students, 19 veterinary schools). Stage 2 was conducted between December 2020 and January 2021 with students from Years 2, 3, 4, and 5 who had experienced both face-to-face and distance education. The scale contained 38 questions, which were divided into seven sub-factors. Most students considered that practical courses (77.1%) should not continue to be delivered by DE; and that catch-up face-to-face programs (77%) would be required for practical skills after the pandemic. The main benefits of DE were that studies did not have to be interrupted (53.2%) and the ability to retrieve online video material for later study (81.2%). A total of 69% of students considered that DE systems and applications are easy to use. Many (71%) students considered that the use of DE would adversely affect their professional skills, 26.5% expected that the duration of their studies would be extended, but only 18.1% had considered suspending their studies for the period of the pandemic. Therefore, it appeared that face-to-face education was considered indispensable by students in veterinary schools, which provide practice-oriented education in the field of health sciences. However, the DE method can be used as a supplementary tool.
Sanal, Sule/0000-0002-5703-5752; Tekindal, Mustafa Agah/0000-0002-4060-7048; Menteş Gürler, Ayşe/0000-0001-8402-7291; Aslım, Gökhan/0000-0001-5976-8186;
Keywords: COVID-19; Distance Education; Online Education; Pandemic; Veterinary Students